Pillar[10]arene‐Based Size‐Selective Host–Guest Complexation and Its Application in Tuning the LCST Behavior of a Thermoresponsive Polymer. Issue 1 (25th November 2014) - Yu, Guocan; Zhou, Jiong; Chi, Xiaodong
<x xml:space="preserve">Abstract</x> A new molecular recognition motif between a water soluble pillar[10]arene (WP10) and 1, 10‐phenanthrolinium guest (G) in water is established. Mainly driven by the cooperativity of multiple electrostatic interactions, hydrophobic interactions, and π–π stacking interactions between WP10 and G, this host–guest complex exhibits a high association constant in water, which is about 17 times higher than that between WP10 and paraquat (PQ). Furthermore, this size selective host–guest complexation is employed to tune the lower critical solution temperature behavior of a random copolymer with PQ derivative pendants. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>